1976
DOI: 10.1136/bmj.1.6025.1555
|View full text |Cite
|
Sign up to set email alerts
|

Course of patients discharged early after myocardial infarction.

Abstract: SummaryTwo hundred and seventy-one (76",,)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…On the morning of discharge (0900 to 1400 hours) the mean grade 225 2I00 1-75j w 1.50 ṽ 125 1-00 0.75 was higher (1-31 +0418) than in the hospital recordings (1-00 ±0416; p <0-05) but was lower than in the equivalent period of the home recording (1-81±0-18; p<0-005). After discharge (1400 to 0900 hours) the mean grade of ventricular arrhythmias in the peri-discharge recording (1-46+0-09) continued to be higher than in the hospital recording 9 (0.96 ±008; p < 0-001) but was similar to that seen in the later home recording (1.59 ±009; p > 0 05) (Fig. 5).…”
Section: Recordingsmentioning
confidence: 57%
“…On the morning of discharge (0900 to 1400 hours) the mean grade 225 2I00 1-75j w 1.50 ṽ 125 1-00 0.75 was higher (1-31 +0418) than in the hospital recordings (1-00 ±0416; p <0-05) but was lower than in the equivalent period of the home recording (1-81±0-18; p<0-005). After discharge (1400 to 0900 hours) the mean grade of ventricular arrhythmias in the peri-discharge recording (1-46+0-09) continued to be higher than in the hospital recording 9 (0.96 ±008; p < 0-001) but was similar to that seen in the later home recording (1.59 ±009; p > 0 05) (Fig. 5).…”
Section: Recordingsmentioning
confidence: 57%
“…Their in-hospital mor tality was from 10 to 18% depending on whether the patient was without or with pul monary edema respectively and 70% in pa tients with hypotension and shock. Gelson et al [13] reported an in-hospital mortality of 15% amongst males with AMI and the mean age of their series was 56.9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 62% could be discharged in accordance with the original plans. In previous studies with 7-9 days' hospital treatment, the corresponding proportion of uncomplicated infarctions has varied between 49 and 76 % (5,7,9). One patient in the 8-day group died on the fourth day and it is difficult to judge whether or not this death could have been prevented by a longer period of bed-rest.…”
Section: Discussionmentioning
confidence: 96%